Pengaruh Jenis Pelarut dan Ukuran Partikel pada Ekstraksi Kulit Buah Kakao (Theobroma cacao L.) menggunakan Metode Microwave Assisted Extraction (MAE) terhadap Karakteristik Ekstrak - Sumantining, Luh Putu Ayu; Ganda Putra, G.P.; Suhendra, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 10 No 1 (2022): Maret, 2022)
This research was conducted to determine the effect of the type of solvent and particle size on the extraction of cocoa pods using the Microwave Assisted Extraction (MAE) method on the characteristics of the extract as a source of antioxidants and to determine the type of solvent and particle size in the extraction of cocoa pods using Microwave Assisted Extraction (MAE) precise in obtaining the highest antioxidant capacity extract. The experimental design used in this study was a factorial randomized block design which was grouped into 2 groups based on the implementation time and consisted of two factors. The first factor is the type of solvent which consists of 3 levels, namely methanol, ethanol and acetone. The second factor is particle size which consists of 3 levels, namely 40 mesh, 60 mesh and 80 mesh. The data were analyzed by analysis of variance and continued with Tukey test . The results showed that the type of solvent and particle size had a very significant effect on the yield, total phenolic, total flavonoid and antioxidant capacity. The interaction between treatments had a very significant effect on total flavonoids and antioxidant capacity, and had a significant effect on total phenolics, but had no significant effect on the yield of cocoa pod peel powder extract. The best treatment to produce cocoa pod peel extract on extraction using MAE was ethanol solvent and particle size 80 mesh with yield characteristics of 12.23±0.61% total phenolic 148.84±0.10 mg GAE/g extract, total flavonoids of 94.16±0.23 mgQE/g extract, and antioxidant capacity of 133.30±0.49 mg GAEAC/g extract. Keywords :   Solvent type, particle size, antioxidants, cocoa pod husk